1988
DOI: 10.1111/j.1471-4159.1988.tb01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Release of Neuronal Serotonin and 5‐Hydroxyindoleacetic Acid in the Caudate‐Putamen of the Rat as Revealed by Intracerebral Dialysis Coupled to High‐Performance Liquid Chromatography with Fluorimetric Detection

Abstract: Extracellular levels of endogenous serotonin (5-HT) and its major metabolite, 5-hydroxyindoleacetic acid (5-HIAA), were measured in the caudate-putamen of anesthetized and awake rats using intracerebral microdialysis coupled to HPLC with fluorimetric detection. A dialysis probe (of the loop type) was perfused with Ringer solution at 2 microliters/min, and samples collected every 30 or 60 min. Basal indole levels were followed for up to 4 days in both intact and 5,7-dihydroxytryptamine (5,7-DHT) lesioned animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(69 citation statements)
references
References 71 publications
9
60
0
Order By: Relevance
“…Increased firing seems reasonable as high cortical dialysate 5-HT and low 5-HIAA values also occur on both handling (Kalen et al, 1989) and stimulation with K+ ( Figure 2). The latter finding agrees with previous dialysis studies (Kalen et al, 1988;Auerbach et al, 1989;Carboni & DiChiara, 1989). It is relevant that transport of 5-HIAA from neurones has been suggested to be impaired during the depolarized state which occurs when 5-HT is actively released (Miyamoto et al, 1990).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Increased firing seems reasonable as high cortical dialysate 5-HT and low 5-HIAA values also occur on both handling (Kalen et al, 1989) and stimulation with K+ ( Figure 2). The latter finding agrees with previous dialysis studies (Kalen et al, 1988;Auerbach et al, 1989;Carboni & DiChiara, 1989). It is relevant that transport of 5-HIAA from neurones has been suggested to be impaired during the depolarized state which occurs when 5-HT is actively released (Miyamoto et al, 1990).…”
Section: Discussionsupporting
confidence: 82%
“…Recent investigations on 5-hydroxytryptamine (5-HT) by Auerbach et al (1989), Kalen et al (1988) and Carboni & DiChiara (1989) show that various drug treatments influence dialysate 5-HT levels in the expected direction. Other studies reveal that levels rise during motor activity or handling (Kalen et al, 1989).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…While TRP availability to the brain influences 5-HT synthesis, 350,351 extracellular 5-HT levels reflect the neuronal activity of release and reuptake of the neurotransmitter. 355 LAC ingestion not only affects 5-HT synthesis, but also its release. Long-term LAC diet was reported to elevate extracellular 5-HT and may induce beneficial effects on mood.…”
Section: Experimental Manipulations Of 5-ht In Relation To Sv Factorsmentioning
confidence: 90%
“…Fluoxetine treatment consistently increased 5-HT levels in most other brain areas: Nearly fourfold in striatum (Perry and Fuller 1992), 2.5-fold in thalamus (Dailey et al 1992), and twofold in diencephalon (Rutter and Auerbach 1993). Among other selective 5-HT uptake inhibitors, indalpine increased 5-HT levels threefold in caudate-putamen (Kalen et al 1988). Sertraline (Invernizzi et al 1991), citalopram (Invernizzi et al 1992, or clomipramine (Adell and Artigas 1991) produced fi.ve-, four-, and threefold increases, respectively, in the rap he areas.…”
Section: Discussionmentioning
confidence: 99%
“…Applications of in vivo techniques (including rnicrodialysis) have demonstrated that extracellular serotonin in most rat brain areas increases several fold over basal levels upon systemic administration of serotonin uptake inhibitors, including fluoxetine (Auerbach et al 1989;Dailey et al 1992;Guan and McBride 1988;Fuller 1992, 1993a;Rutter and Auerbach 1993), indalpine (Kalen et al 1988(Kalen et al ), citaloprarn (lnvernizzi et al 1992, sertraline (Invernizzi et al 1991), and clomipramine (Adell and Artigas 1991;Carboni and Di Chiara 1989). Extracellular norepinephrine (NE) concentrations are also elevated upon local or peripheral administra-tion of the NE uptake inhibitor desipramine (Dennis et al 1987;Itoh et al 1990;Kalen et al 1988;L'Heureux et al 1986;Thomas and Holman 1991).…”
Section: Mg/kg Produced Less Pronounced Increases While No Consistentmentioning
confidence: 99%